Protocol for Correcting Residual Errors with Spectral, ULtrasound, Traditional Speech therapy Randomized Controlled Trial (C-RESULTS RCT) - Tara McAllister; Jonathan L. Preston; Elaine R. Hitchcock; Jennifer Hill (BMC, 2020)
Abstract Background Speech sound disorder in childhood poses a barrier to academic and social participation, with potentially lifelong consequences for educational and occupational outcomes. While most speech errors resolve by the late school-age years, between 2 and 5% of speakers exhibit residual speech errors (RSE) that persist through adolescence or even adulthood. Previous findings from small-scale studies suggest that interventions incorporating visual biofeedback can outperform traditional motor-based treatment approaches for children with RSE, but this question has not been investigated in a well-powered randomized controlled trial. Methods/design This project, Correcting Residual Errors with Spectral, ULtrasound, Traditional Speech therapy Randomized Controlled Trial (C-RESULTS RCT), aims to treat 110 children in a parallel randomized controlled clinical trial comparing biofeedback and non-biofeedback interventions for RSE affecting the North American English rhotic sound /ɹ/. Eligible children will be American English speakers, aged 9-15 years, who exhibit RSE affecting /ɹ/ but otherwise show typical cognitive-linguistic and hearing abilities. Participants will be randomized, with stratification by site (Syracuse University or Montclair State University) and pre-treatment speech production ability, to receive either a motor-based treatment consistent with current best practices in speech therapy (40% of participants) or treatment incorporating visual biofeedback (60% of participants). Within the biofeedback condition, participants will be assigned in equal numbers to receive biofeedback in the form of a real-time visual display of the acoustic signal of speech or ultrasound imaging of the tongue during speech. The primary outcome measure will assess changes in the acoustics of children's production of /ɹ/ during treatment, while a secondary outcome measure will use blinded listeners to evaluate changes in the perceived accuracy of /ɹ/ production after the completion of all treatment. These measures will allow the treatment conditions to be compared with respect to both efficacy and efficiency. Discussion By conducting the first well-powered randomized controlled trial comparing treatment with and without biofeedback, this study aims to provide high-quality evidence to guide treatment decisions for children with RSE. Trial registration ClinicalTrials.gov identifier NCT03737318, November 9, 2018.